1991
DOI: 10.1002/hep.1840130417
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of postprandial hyperemia in superior mesenteric artery and portal vein in healthy and cirrhotic humans: An operator-blind echo-Doppler study

Abstract: In an operator-blind design, we used an echo-Doppler duplex system to examine superior mesenteric artery and portal vein hemodynamics on two consecutive mornings in 12 fasting cirrhotic patients and 12 matched controls, randomized to a standardized 355 kcal mixed-liquid meal vs. water. Cross-sectional area and mean velocity were recorded from the portal vein and superior mesenteric artery at 30 min intervals, from 0 min to 150 min after ingestion. Flows were calculated. Pulsatility index, an index related to v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
42
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 106 publications
(48 citation statements)
references
References 18 publications
6
42
0
Order By: Relevance
“…Therefore, it is important to identify patients who experience increased postprandial hyperemic response, and treat these patients appropriately. EchoDoppler ultrasonography is a non-invasive test which is widely used to determine portal blood flow [4,7,8,10] In an observer-blinded study, it was shown that echo- Figure 1 Positive correlation between the portal blood velocity (PBV) and hepatic venous pressure gradient (HVPG ) (r = 0.8, P < 0.05). Figure 2 Inverse correlation between the superior mesenteric artery pulsatility index (SMA-PI) and hepatic venous pressure gradient ( HVPG) (r = -1, P < 0.01).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, it is important to identify patients who experience increased postprandial hyperemic response, and treat these patients appropriately. EchoDoppler ultrasonography is a non-invasive test which is widely used to determine portal blood flow [4,7,8,10] In an observer-blinded study, it was shown that echo- Figure 1 Positive correlation between the portal blood velocity (PBV) and hepatic venous pressure gradient (HVPG ) (r = 0.8, P < 0.05). Figure 2 Inverse correlation between the superior mesenteric artery pulsatility index (SMA-PI) and hepatic venous pressure gradient ( HVPG) (r = -1, P < 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…These measurements were obtained from the longitudinal section of the vessel by positioning the sample volume cursor over the vessel at a known angle of insonation, defined as an angle between the Doppler beam and the long axis of the vessel. The Doppler sample volume probe was positioned over the middle of the vessel and was manipulated to cover about 90% of the vessel section in order to detect the maximum Doppler frequency shift, related to the maximum velocity (4).…”
Section: Echo-doppler Usgmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3] More recently, other parameters have been suggested for the study of the hepatic and superior mesenteric arteries, in which blood flow may be altered by liver diseases affecting mesenteric and hepatic arterial resistances. [4][5][6] It has been shown that portal as well as hepatic and splanchnic arterial Doppler parameters are significantly different in patients with liver disease and healthy subjects. However, few data are available regarding the relationship between these parameters and the severity of portal hypertension or the impairment of liver function in patients with cirrhosis.…”
mentioning
confidence: 99%